Funny enough, they all think of themselves as rational and intelligent human beings, but they don’t act humanely, behave rationally, or think sensibly. They can be categorized into three classes: A. Men. When they talk of love, they mean sex. B. Women. When they talk of love, they mean money. C. 2SLGBTQIA+. When they talk about sex, nobody knows what they are talking about, Apocalypse, Anawim, #justtothepoint.com

Recall that two groups (G, *) and (G', ⋄) are said to be isomorphic if there exist a bijective homomorphism, i.e., a one-to-one and onto map Φ: G → G’ such that the group operation is preserved, that is, ∀x, y ∈ G : ϕ(x ∗ y) = ϕ(x) ⋄ ϕ(y).

Suppose that Φ is an isomorphism between two groups, Φ: G → G’. Then,

- Isomorphism carries or preserves the identity.

Proof:
Φ(e) =[G group, ∃e identity e·e = e] Φ(e·e) =[Φ is isomorphism, the group operation is preserved] Φ(e)·Φ(e) ⇒ Φ(e) = Φ(e)·Φ(e) ⇒ [By cancellation property, ab = ac ⇒ b = c Λ Φ(e) = Φ(e)·Φ(e)] **e’ = Φ(e).**

- ∀n ∈ ℤ, ∀a ∈ G, Φ(a
^{n}) = (Φ(a))^{n}.

Proof:

n = 0, Φ(a^{0}) = Φ(e) = [Previous result] e’ = Φ(a)^{0}.

n = 1, Φ(a^{1}) = Φ(a) = Φ(a)^{1}. Trivial

n = 2, Φ(a^{2}) = Φ(a·a) = [isomorphism, the group operation is preserved] Φ(a)Φ(a) = (Φ(a))^{2}. Let’s apply induction on n.

Φ(a^{n+1}) = Φ(a^{n}a) = [Φ is isomorphism] Φ(a^{n})Φ(a) = [By Inductive hypothesis] (Φ(a))^{n}Φ(a) = (Φ(a))^{n+1}.

n ≤ 0, -n ≥ 0, e’ = Φ(e) = Φ(a^{n}a^{-n}) = Φ(a^{n})Φ(a^{-n}) = [We have already demonstrated for all positive integers Λ -n ≥ 0] Φ(a^{n})(Φ(a))^{-n} ⇒ [e’ = Φ(a^{n})(Φ(a))^{-n} and multiplying both sides by (Φ(a))^{n}] (Φ(a))^{n} = Φ(a^{n})∎

- Isomorphism preserves commutativity.

Proof:

⇒) Suppose (G, ·) is Abelian, ∀a,b: a·b = b·a. Besides, ∀a’, b’ ∈ G’: ∃a, b ∈ G: Φ(a) = a’, Φ(b) = b'.

a’·b’ = [Φ is onto] Φ(a)·Φ(b) = [Φ is isomorphism ⇒ homomorphism] Φ(a·b) = [By assumption, (G, ·) is Abelian, a·b = b·a] Φ(b·a) = [Φ is homomorphism] Φ(b)·Φ(a) = b’·a’ ⇒ (G’, ·) is Abelian.

⇐) Suppose G’ is Abelian and for the sake of contradiction, assume G is not Abelian ⇒ ∃a, b ∈ G: a·b ≠ b·a ⇒ [Φ is injective] Φ(a·b) ≠ Φ(b·a) ⇒ [Φ is homomorphism] Φ(a)·Φ(b) ≠ Φ(b)·Φ(a) ⊥ (G’ is not Abelian).

- Isomorphism between cyclic groups carries the generator, i.e.,
**G = ⟨a⟩ if and only if G’ = ⟨Φ(a)⟩**.

Proof: Suppose G = ⟨a⟩ ⇒ [Φ(a) ∈ G’ and (G’, ·) group, so by closure, Φ(a)·Φ(a)∈ G’. In general, Φ(a)^{n} ∈ G’] ⟨Φ(a)⟩ ⊆ G’. Since Φ is onto, ∀b ∈ G’, ∃k ∈ℤ such that a^{k} ∈ G Λ Φ(a^{k}) = b ⇒ b = Φ(a^{k}) = [∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] (Φ(a))^{k} ∈ ⟨Φ(a)⟩ ⇒ ∀b ∈ G’, ∃k ∈ℤ such that b = (Φ(a))^{k} ∈ ⟨Φ(a)⟩ ⇒ G’ ⊆ ⟨Φ(a)⟩ ⇒ ⟨Φ(a)⟩ = G'.

Suppose G’ = ⟨Φ(a)⟩ ⇒ [a ∈ G, (G, ·) group, and by closure] ⟨a⟩ ⊆ G. ∀b ∈ G, Φ(b) ∈ G’ = ⟨Φ(a)⟩ ⇒ ∃k ∈ℤ, Φ(b) = (Φ(a))^{k} = [∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] Φ(a^{k}), so Φ(b) = Φ(a^{k}) ⇒ [Φ is one-to-one] b = a^{k} ∈ G ⇒ ∀b ∈ G ∃k∈ℤ such that b = a^{k} ⇒ G ⊆ ⟨a⟩ ⇒ ⟨a⟩ = G ∎

- Isomorphism preserves the order of an element, i.e.,
**∀a ∈ G, |a| = |Φ(a)|.**

Proof: Suppose that G and G’ are finite, |a| = n and |Φ(a)| = m.

|a| = n ⇒ Φ(a^{n}) = Φ(e) = [Φ carries the identity] e’, and Φ(a^{n}) = [∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] Φ(a)^{n} = e’ ⇒ [By assumption, |Φ(a)| = m] m ≤ n.

|Φ(a)| = m ⇒ (Φ(a))^{m} = [∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] Φ(a^{m}) = e’. Therefore, Φ(a^{m}) = Φ(a^{n}) = e’ ⇒ [Φ is one-to-one] a^{n} = a^{m} = e ⇒ [By assumption, |a| = n] n ≤ m ⇒ n = m.

Suppose that |a| = n and |Φ(a)| = ∞ ⇒ a^{n} = e ⇒ [Φ carries the identity] Φ(a^{n}) = e’ ⇒ (Φ(a))^{n} = e’ ⊥

Suppose that |a| = ∞ and |Φ(a)| = n ⇒ (Φ(a))^{n} = e’ ⇒ Φ(a^{n}) = e’, but we already know that [Φ carries the identity] Φ(e) = e’, and Φ is one-to-one ⇒ a^{n} = e ⊥

- If two groups are isomorphic, then corresponding equations have the same number of solutions. For a fixed k ∈ ℤ and a fixed b ∈ G, the equation x
^{k}= b has the same number of solutions in G as does the equation x^{k}= Φ(b) in G'.

Proof: Let A be the set of all solutions to x^{k} = b.

∀a ∈ A: a^{k} = b ⇒ Φ(a^{k}) = Φ(b) ⇒ Φ(a)^{k} = Φ(b). Therefore, the image Φ(A) is a subset of all solutions to x^{k} = Φ(b).

Let q’ ∈ G’ be a solution to x^{k}= Φ(b) in G’: q’^{k} = Φ(b). Since Φ is onto, ∃q ∈ G: Φ(q) = q’, and therefore, (Φ(q))^{k} = Φ(q^{k}) = Φ(b) ⇒ Φ(q^{k}) = Φ(b) ⇒ [Φ is one-to-one] q^{k} = b ⇒ q ∈ A ⇒ q’=Φ(q) ∈ Φ(A) ⇒[q’ ∈ G’ be an arbitrary solution to x^{k}= Φ(b) in G’] **Φ(A) is equal to the set of all solutions to x ^{k} = Φ(b)**, and since Φ is an isomorphism |A|=|Φ(A)|.

ℂ* and ℝ* are not isomorphic because the equation x^{4} = 1 has four solution in ℂ* (1, -1, i,-i), but only two in ℝ*.

Suppose that Φ is an isomorphism between two groups, Φ: G → G’. Then,

- Φ
^{-1}is an isomorphism from G' onto G.

- Φ is bijective ⇒ [A function is bijective if and only if has an inverse] Φ
^{-1}exists and is also bijective. - Suppose a’, b’ ∈ G’ ⇒[Φ is isomorphism] ∃a, b ∈ G: Φ(a) = a’, Φ(b) = b’⇒ Φ
^{-1}(a’b’) = Φ^{-1}(Φ(a)Φ(b)) = [Φ is a isomorphism] Φ^{-1}(Φ(ab)) = ab = Φ^{-1}(a’)Φ^{-1}(b’).

**|G| = |G’|**- G is Abelian if and only if G' is Abelian

- Suppose G is Abelian, ∀a’, b’ ∈ G’ ⇒ ∃a, b ∈ G: Φ(a) = a’, Φ(b) = b’, a’b’ = Φ(a)Φ(b) = [Φ is a group homomorphism] Φ(ab) = [By assumption, G is Abelian] Φ(ba) =[Φ is a group homomorphism] Φ(b)Φ(a) = b’a'
- Suppose G’ is Abelian, ∀a, b ∈ G, Φ(ab) =[Φ is a group homomorphism] Φ(a)Φ(b) = [G’ is Abelian] Φ(b)Φ(a) = [Φ is a group homomorphism] = Φ(ba), therefore Φ(ab) = Φ(ba) ⇒ [Φ is one-to-one] ab = ba

- G is cyclic if and only if G' is cyclic

- Suppose G is cyclic. G = ⟨g⟩. Let a’∈ G’ ⇒ ∃a ∈ G, ∃n ∈ ℤ, Φ(a) = a’ and a = g
^{n}⇒ a’ = Φ(g^{n}) =[∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] (Φ(g))^{n}⇒ ∀a’∈ G’, ∃n ∈ ℤ, such that a’ = (Φ(g))^{n}⇒ G’ = ⟨Φ(g)⟩. - Suppose G’ is cyclic. G’ = ⟨g’⟩ ⇒ ∃ g ∈ G: g’ = Φ(g). Let a ∈ G ⇒ [G’ = ⟨g’⟩] Φ(a) = g’
^{n}for some n ∈ ℤ = (Φ(g))^{n}=[∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] Φ(g^{n}) ⇒ Φ(a) = Φ(g^{n}) ⇒ [Φ is one-to-one] a = g^{n}⇒ ∀a∈G, a = g^{n}for some n ∈ ℤ ⇒ G = ⟨g⟩∎

- If G has a subgroup H, then Φ(H) = {Φ(h) | h ∈ H} is a subgroup of G', i.e.,
**H ≤ G ⇒ Φ(H) ≤ G’**.

Proof: We know that Φ(H) ⊆ G’, is Φ(H) a subgroup of G'?

∀a’, b’ ∈ Φ(H) ⇒ ∃a, b ∈ H: Φ(a) = a’, Φ(b) = b’ ⇒ [H is a subgroup] a·b^{-1} ∈ H ⇒ Φ(a·b^{-1}) =[Φ is a group homomorphism] Φ(a)Φ(b^{-1}) =[∀n ∈ ℤ, ∀a ∈ G, Φ(a^{n}) = (Φ(a))^{n}] Φ(a)(Φ(b))^{-1} = a’b’^{-1} ∈ Φ(H) ⇒ ∀a’, b’ ∈ Φ(H), a’b’^{-1} ∈ Φ(H) ⇒ Φ(H) ≤ G’ ∎

- Isomorphism of groups is an equivalence relation.

Proof.

- Reflexive. G ≋ G because a group is isomorphic to itself, Φ: G → G, ∀a ∈ G, Φ(a) = a, i.e., Φ is the identity.
- Symmetric Property. If G ≋ G’ via Φ, then G’ ≋ G via Φ
^{-1}. - Transitivity. If G ≋ H via Φ and H ≋ K via φ, then Φφ: G → K is an isomorphism, i.e., G ≋ K.

Proof: The composition of two bijections is a bijection, too. Besides, (Φφ)(g_{1}g_{2}) = Φ(φ(g_{1}g_{2})) = [φ is a group homomorphism] Φ(φ(g_{1})φ(g_{2})) = [Φ is a group homomorphism] Φ(φ(g_{1}))Φ(φ(g_{2})) = (Φφ)(g_{1})(Φφ)(g_{2})∎

This content is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License. This post relies heavily on the following resources, specially on NPTEL-NOC IITM, Introduction to Galois Theory, Michael Penn, and Contemporary Abstract Algebra, Joseph, A. Gallian.

- NPTEL-NOC IITM, Introduction to Galois Theory.
- Algebra, Second Edition, by Michael Artin.
- LibreTexts, Abstract and Geometric Algebra, Abstract Algebra: Theory and Applications (Judson).
- Field and Galois Theory, by Patrick Morandi. Springer.
- Michael Penn (Abstract Algebra), and MathMajor.
- Contemporary Abstract Algebra, Joseph, A. Gallian.
- Andrew Misseldine: College Algebra and Abstract Algebra.